BIOLOGICAL CHARACTERS OF SNAKEHEAD GUDGEON (Giuris margaritacea Valenciennes, 1837) IN TONDANO LAKE, MINAHASA, NORTH SULAWESI, INDONESIA - Makmur, Safran; Muthmainnah, Dina; Subagdja, Subagdja (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2019)
Snakehead gudgeon (Giuris margaritacea) or Payangka in Indonesian’s local name, has a high population and been used as a consumption fish mainly by people around Lake Tondano, not only the consumption size, but also the juvenile (it called Nike) are preferred. The fish resources are the essential source and need to keep their sustainable in the future. The research was carried out in 2015. The study was aimed to identify and record some aspects of snakehead gudgeon fish biology in Lake Tondano Mi-nahasa Regency of North Sulawesi. Fish samples were obtained from fisher's catch. The morphometric and meristic character was measured, and also was performed surgery to observe reproduction and food. The results showed that the growth pattern of Giuris margaritacea was positive allometric with sex ratio 1: 1.41. The fish was spawning whole year with fecundity between 36,892-90,102 eggs, and diameter of the egg was 0.285 mm on average. The size of the first mature female was 10.75 cm gonads. Snakehead gudgeon was a carnivorous fish with shrimp as the primary food, and the relative length of the digestive tract was 82.88%.